ESTIMATING THE POTENTIAL FOR CONJUNCTIVE WATER MANAGEMENT IN COASTAL PLAINS - N. Cao Don; H. Araki; N. T. Minh Hang; H. Yamanishi; K. Koga (Lowland Technology International, 2006)
This paper presents the development and application of a conjunctive water management model for lowland catchments. The model incorporates a simulation model and a management model to simulate groundwater movement, ground consolidation and to search for the potential pumping amount of groundwater without violating physical and environmental constraints. The results reveal that groundwater levels in a coastal aquifer greatly vary in response to pumping. Consequently subsidence rapidly occurs throughout the area. The study also suggests that conjunctive water management can be used to improve water supply reliability, to reduce groundwater overdraft and land subsidence and to improve environmental conditions.